Dysprosium Single‐Molecule Magnets with Bulky Schiff Base Ligands: Modification of the Slow Relaxation of the Magnetization by Substituent Change. Issue 2 (6th December 2018) - Long, Jérôme; Basalov, Ivan V.; Forosenko, Natalia V.; Lyssenko, Konstantin A.; Mamontova, Ekaterina; Cherkasov, Anton V.; Damjanović, Marko; Chibotaru, Liviu F.; Guari, Yannick; Larionova, Joulia; Trifonov, Alexander A.
Abstract: The synthesis, and magnetic and photoluminescence investigations of two bifunctional dysprosium complexes based on tridentate Schiff base ligands is reported. Magnetic investigations reveal a genuine single‐molecule magnet (SMM) behavior, with out‐of‐phase signals up to 60 K, and tunable emission arising from the Schiff base ligands. Abstract : Slowly but surely : Schiff base dysprosium complexes exhibit single‐molecule magnet behavior with out‐of‐phase signals up to 60 K and tunable emission.